THE METHOD OF CONSTRUCTION OF THE SPRAYING OF THE CONCRETE LINING IN THE VERTICAL OPENINGS - Borshchevskyi, S. V.; Kamenets, V. I.; Driuk, O. O. (Science and Transport Progress, 2008)
The method of building the spill-concrete walls in mine holes of large diameter is analyzed. The variant of calculation of thickness of spill-concrete walls using such a method is offered. The recommendation on perfection of technology of timbering the mine holes of large diameter with a purpose of providing the durability and cost efficiency during the building of walls in vertical mines is proposed.